2020
DOI: 10.1186/s12879-020-05149-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing clinical outcomes of piperacillin-tazobactam administration and dosage strategies in critically ill adult patients: a systematic review and meta-analysis

Abstract: Background: Recently, continuous administration of piperacillin-tazobactam has been proposed as a valuable alternative to traditional intermittent administration especially in critically ill patients. However, antibiotic dosing remains a challenge for clinicians as antibiotic dosing regimens are usually determined in non-critically ill hospitalized adult patients. The aim was to conduct a systematic review to identify and highlight studies comparing clinical outcomes of piperacillin tazobactam dosing regimens,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…After the DALI-study revealed that underdosing of beta-lactam antimicrobials was common in critically ill patients, several dose optimization strategies, such as higher maintenance doses and the use of continuous infusions, were developed and implemented [ 25 ]. These strategies were also used during this study, resulting in almost all samples attaining the minimum—conservative—clinical target set forward by the joint ESICM/IATDMCT/ISAC position paper for beta-lactam antimicrobials given by continuous infusion: a measured steady state concentration above the BP [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the DALI-study revealed that underdosing of beta-lactam antimicrobials was common in critically ill patients, several dose optimization strategies, such as higher maintenance doses and the use of continuous infusions, were developed and implemented [ 25 ]. These strategies were also used during this study, resulting in almost all samples attaining the minimum—conservative—clinical target set forward by the joint ESICM/IATDMCT/ISAC position paper for beta-lactam antimicrobials given by continuous infusion: a measured steady state concentration above the BP [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent systematic review and meta-analysis evaluated articles published between 1998 to 2019 showed that there is a significant level of evidence that clinical outcome in critically ill patients is improved in patients receiving piperacillin-tazobactam via continuous/prolonged infusion 25 . Also, Yang et al in their meta-analysis study showed a superior clinical success rate for the continuous infusion (being used over 24 h) than the conventional intermittent approach (over 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Клинические исследования подтверждают результаты, полученные в эксперименте. Так, метаанализ результатов 23 клинических исследований эффективности пролонгированных инфузий пиперациллина/тазобактама (Fawaz S. et al, 2020), включавший в общей сложности 3828 взрослых пациентов в критическом состоянии, продемон-стрировал, что непрерывные/длительные инфузии у пациентов в критическом состоянии статистически достоверно увеличивали частоту клинического излечения (отношение шансов (ОШ) 1,56, 95 % ДИ 1,28-1,90, р=0,0001), снижали показатели смертности (ОШ 0,68, 95 % ДИ 0,55-0,84, р=0,0003), увеличивали вероятность микробиологического излечения (ОШ 1,52, 95 % ДИ 1,10-2,11, р=0,01) и приводили к сокращению сроков госпитализации (средняя разница -1,27 дня, 95 % ДИ 2,45-0,08, р=0,04) [35].…”
Section: стратегии дозированияunclassified